Iterative Cellular Screening System for Nanoparticle Safety Testing. (19th August 2015) - Sambale, Franziska; Stahl, Frank; Rüdinger, Ferdinand; Seliktar, Dror; Kasper, Cornelia; Bahnemann, Detlef; Scheper, Thomas
Abstract : Nanoparticles have the potential to exhibit risks to human beings and to the environment; due to the wide applications of nanoproducts, extensive risk management must not be neglected. Therefore, we have constructed a cell-based, iterative screening system to examine a variety of nanoproducts concerning their toxicity during development. The sensitivity and application of various cell-based methods were discussed and proven by applying the screening to two different nanoparticles: zinc oxide and titanium dioxide nanoparticles. They were used as benchmarks to set up our methods and to examine their effects on mammalian cell lines. Different biological processes such as cell viability, gene expression of interleukin-8 and heat shock protein 70, as well as morphology changes were investigated. Within our screening system, both nanoparticle suspensions and coatings can be tested. Electric cell impedance measurements revealed to be a good method for online monitoring of cellular behavior. The implementation of three-dimensional cell culture is essential to better mimic in vivo conditions. In conclusion, our screening system is highly efficient, cost minimizing, and reduces the need for animal studies.